2016
DOI: 10.3102/0002831216630407
|View full text |Cite
|
Sign up to set email alerts
|

What Does It Mean to Be Ranked a “High” or “Low” Value-Added Teacher? Observing Differences in Instructional Quality Across Districts

Abstract: Education agencies are evaluating teachers using student achievement data. However, very little is known about the comparability of test-based or “value-added” metrics across districts and the extent to which they capture variability in classroom practices. Drawing on data from four urban districts, we found that teachers were categorized differently when compared within versus across districts. In addition, analyses of scores from two observation instruments, as well as qualitative viewing of lesson videos, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…So too might high-quality instruction vary for specific populations of students, such as English learners or special education students. Indeed, prior research has demonstrated that student demographics are associated with both VAMs (Loeb, Soland, & Fox, 2014;Master, Loeb, Whitney, & Wyckoff, 2012) as well as instructional practices (Blazar, Litke, & Barmore, 2016;Grossman et al, 2014).The limited existing evidence around stability of instructional quality across student subpopulations suggests this is an important next step for research on observational instruments, particularly as they are used in high-stakes contexts. From processproduct research (Brophy et al, 1975;Rosenshine, 1970) to more contemporary work (Abedi, Hofstetter, & Lord, 2004;Cohen & Grossman, 2016;Goldenberg, 2008;Grossman et al, 2014;Ladson-Billings, 2009), studies have found teachers' instructional approaches differ depending on the students.…”
mentioning
confidence: 99%
“…So too might high-quality instruction vary for specific populations of students, such as English learners or special education students. Indeed, prior research has demonstrated that student demographics are associated with both VAMs (Loeb, Soland, & Fox, 2014;Master, Loeb, Whitney, & Wyckoff, 2012) as well as instructional practices (Blazar, Litke, & Barmore, 2016;Grossman et al, 2014).The limited existing evidence around stability of instructional quality across student subpopulations suggests this is an important next step for research on observational instruments, particularly as they are used in high-stakes contexts. From processproduct research (Brophy et al, 1975;Rosenshine, 1970) to more contemporary work (Abedi, Hofstetter, & Lord, 2004;Cohen & Grossman, 2016;Goldenberg, 2008;Grossman et al, 2014;Ladson-Billings, 2009), studies have found teachers' instructional approaches differ depending on the students.…”
mentioning
confidence: 99%
“…Whereas many have appraised the Finnish Model, comments and interpretations on the use of VAM usually consist to a great extent of question marks and cautions (American Educational Research Association, 2015;Baker et al, 2010;Darling-Hammond, 2015;Goldhaber, 2015). Recently, some researchers have drawn attention to the variation that emerges in teacher VAM rankings in relation to within and across different school districts (Blazar, Litke, & Barmore, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Observing Differences in Instructional Quality Across Districts", can be found here: https://cepr.harvard.edu/publications/meaning-high-and-lowvalue-added-teaching-observing-differences-instructional. Our work also explored the comparability of testbased or value-added metrics across districts and the extent to which they capture variability in classroom practice (Blazar, D., Litke, E., & Barmore, J., 2016). We found positive though weak correlations between value-added and observation-based measures of teacher performance (Chin, M. & Goldhaber, D., 2015).…”
Section: Using Video To Advance Our Understanding Of Teacher Effectivmentioning
confidence: 90%